Effect of TiB2 content on microstructural features and hardness of TiB2/AA7075 composites manufactured by LMD. (May 2020) - Lei, Zhenglong; Bi, Jiang; Chen, Yanbin; Chen, Xi; Tian, Ze; Qin, Xikun
Abstract: The metal matrix composites (MMCs) manufactured by additive manufacturing (AM) are widely used in aerospace, automobile and other industries for their lightweight and excellent mechanical properties. As a novel and promising AM technology, laser melting deposition (LMD), was utilized to prepare the TiB2 particle reinforced AA7075 composites. The influence of TiB2 content on the microstructural features and microhardness of the composites was studied. The results showed that, after the incorporation of TiB2, the grain size decreased due to heterogeneous nucleation and the solid-liquid interphase pushing and capture effect. Relative to the unreinforced 7075 Al specimen, the TiB2 /AA7075 composites exhibited a higher hardness. For the specimen reinforced with 4 wt% TiB2, the hardness increased to 127.8 HV, and the grain size decreased to 16.8 μm. The microstructure and hardness of the TiB2 /AA7075 composites were significantly enhanced by the incorporation of TiB2 .